2015
DOI: 10.1556/jfc-d-14-00035
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Support Properties on the Activity of Basic Catalysts for Aldol Condensation of Formaldehyde and Methyl Acetate in a Continuous Flow Reactor

Abstract: The aldol condensation of methyl acetate with formaldehyde to form methyl acrylate was studied in a continuous-flow reactor using a series of supported cesium basic catalysts with commercially available materials (ZSM-5, SiO 2 , and γ-Al 2 O 3 ) as carriers prepared by vacuum impregnation. The catalysts were characterized by N 2 adsorption-desorption, Fourier transform-infrared (FT-IR), X-ray diffraction (XRD), and temperature-programmed desorption of ammonia and carbon dioxide (NH 3 /CO 2 -TPD). The obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Still, lots of by-products were detected over HBeta zeolites. Although the acidic sites were reported to be essential to improve the aldol condensation [4,14] , strong acidic sites lead to many side reactions such as olefin polymerization and cracking to increase by-product and coke contents. After nitridation, formaldehyde conversion and methyl acrylate selectivity increase to 97% and 94%, respectively, over NBeta catalyst.…”
Section: Aldol Condensation Catalyzed By Nbeta Zeolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, lots of by-products were detected over HBeta zeolites. Although the acidic sites were reported to be essential to improve the aldol condensation [4,14] , strong acidic sites lead to many side reactions such as olefin polymerization and cracking to increase by-product and coke contents. After nitridation, formaldehyde conversion and methyl acrylate selectivity increase to 97% and 94%, respectively, over NBeta catalyst.…”
Section: Aldol Condensation Catalyzed By Nbeta Zeolitesmentioning
confidence: 99%
“…At present, aldol condensation reactions are mainly carried out on solid catalysts, including acidic [4,8,9] , basic [5,10] , and acid-base bifunctional catalysts [11][12][13] . Solid acidic catalysts mainly include phosphates [8] and zeolites [9,14] . Khalameida et al reported titanium phosphates for aldol condensation of acetic acid and formaldehyde with an acrylic acid selectivity of 80% [8] .…”
Section: Introductionmentioning
confidence: 99%
“…A new potential way to synthesize MA using methyl acetate (Ma) with formaldehyde (FA) by vapor phase aldol condensation in a one-step process (Scheme ) has been developed. , Solid base and acid–base catalysts with cesium as the main active component that supported porous silica, alumina, magnesia, and zeolites showed good activity for aldol condensation reactions. Yan et al reported a 48.4 mol % conversion of Ma and 95.0 mol % selectivity of MA over Cs/SBA-15 catalyst in a single-pass, fixed-bed, and flow reactor. Wang et al reported a series of supported cesium basic catalysts with commercially available materials (ZSM-5, SiO 2 , and γ-Al 2 O 3 ) as support for aldol condensation of FA and Ma in a continuous-flow reactor. Ai found that Cs–Si catalyst exhibited the best catalytic performance for the formation of methyl methacrylate (MMA) from aldol condensation of FA and propionic acid (PA), with a continuous-flow system.…”
Section: Introductionmentioning
confidence: 99%
“…11−17 Yan et al 7 reported a 48.4 mol % conversion of Ma and 95.0 mol % selectivity of MA over Cs/ SBA-15 catalyst in a single-pass, fixed-bed, and flow reactor. Wang et al 12 reported a series of supported cesium basic catalysts with commercially available materials (ZSM-5, SiO 2 , and γ-Al 2 O 3 ) as support for aldol condensation of FA and Ma in a continuous-flow reactor. Ai 13 found that Cs−Si catalyst exhibited the best catalytic performance for the formation of methyl methacrylate (MMA) from aldol condensation of FA and propionic acid (PA), with a continuous-flow system.…”
Section: Introductionmentioning
confidence: 99%